PENGUJIAN AKTIVITAS ANTIOKSIDAN SHATA DHAUTA GHRITA DENGAN PENCUCIAN MENGGUNAKAN INFUSED WATER DAUN KAYU MANIS BALI - Sanjiwani, Ni Made Sukma; Wibawa, Agung Ari Chandra; Rahadi, I Wayan Surya; Mariati, Ni Putu Ayu Mirah; Vinanda, Ketut Adelia; Pradnyandari, I Gusti Ayu Agung Ratih (LPPM, Institut Teknologi Sepuluh Nopember, 2024)
Shata Dhauta Ghrita (SDG) is a basic medicinal preparation for external use or cream. SDG originally had the definition of Ghrita washed a hundred times with water [14]. This study aims to make Shata Dhauta Ghrita with washing using greentea-scented cinnamon leaf infused water. Shata Dhauta Ghrita with washing using cinnamon leaf infused water with greentea aroma was analyzed for antioxidant activity and antioxidant testing optimization was carried out, namely looking for optimal conditions and results. In this study, infused water was made first, then butter, ghee and shata dhauta ghritanya were made, making shata dhauta ghritanya using washing with cinnamon leaf infused water and flavored with green tea. Testing antioxidant activity with DPPH method: Weighed 25 mg of sample dissolved with a little methanol p.a, then put into a 25 milliliter volumetric flask, the volume is sufficient to indicate the limit and homogenized (1000 µg/ml). 0.5 ml of filtrate was taken and 3.5 ml of 0.1 mM DPPH solution was added in the test tube. The test solution was allowed to stand for 30 minutes at room temperature and dark area then measured the absorbance at the maximum wavelength using UV-Vis spectrophotometer. The antioxidant activity test of shata dhauta ghrita has an IC50 value of 22,445.1 which means it has very strong antioxidant activity. This very strong antioxidant activity is because shata dhauta ghrita has active substances, namely flavonoids, because the washing uses cinnamon leaf infused water. Shata dhauta ghrita has an IC50 value of 22,445.1 which means it has very strong antioxidant activity.